Effectiveness of Rosetta Stone Software in learning the english language promoted by UDELAS in the special english program (PEI) 2009 - Atencio, Ericka; Concepción, Stephany; Bennett, David; Quintero, Lourdes; De Lisser, Mónica; Araúz, Clemente (David, Panamá : UDELAS, 2010)
As it is well known, english is an important tool, and is one of the keys to success in today'ss world, either business or cultual. The Universidad Especilizada de las Americas works to prepare their students with best tools, and implementing the use of the Rosetta Stone software to a better level of english language acquisition is one of the strategies.
TABLE OF CONTENTS Dedication Acknowledgment INTRODUCCIÓN CHAPTER I STATEMENT OF THE PROBLEM CHAPTER THEORETICAL FRAMEWORK CHAPTER III RESEARCH METHODOLOGY CHAPTER IV: PRESENTATION OF RESULTS CHAPTER V CONCLUSIONS AND RECOMMENDATIONS CHAPTER VI REFERENCES AND ANNEXES REFERENCES ANNEXES
Incluye Table of contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; LICENCIATURA EN DOCENCIA EN INGLÉS; ROSETTA STONE SOFTWARE; SPECIAL ENGLISH PROGRAM (PEI)